Production of lactic acid from simultaneous saccharification and fermentation of base-pretreated rice bran - Agutaya, Jonas Karl Christopher N.; Gonzaga, Lean Robert A.; Tabano, Luther Debu M.; Mariano, Victor; Baynosa, Marjorie (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
Lactic acid has many industrial applications. The presence of hydroxyl and carboxylic groups in this organic acid makes it suitable as a general food additive and as a pH regulator in cosmetic products. This acid is also used as a monomer in the synthesis of polylactic acid, a biodegradable plastic.Most industries require optically pure lactic acid, particularly the polymer industry. Since only fermentative synthesis can produce lactic acid in its pure chiral form, this method is commonly employed in many manufacturing plants. In the fermentative synthesis of lactic acid, a population of microorganisms is used to convert a substrate to metabolites. Lactobacillus delbrueckii is the common choice as microorganism because this species produces lactic acid with no secondary products.The problem in fermentative synthesis is the prohibitive cost of the raw materials. Many researches on the use of rice bran in the lactic acid production have been recently published in the recent decade. Gao, et al (2008) studied the utilization of rice bran as a nutrient source for fermentative lactic acid production. Taniguchi, et al (2005) produced L-lactic acid using unsterilized defatted rice bran as the carbon source and a nutrient component. Meanwhile, tanaka, et al (2006) produced D-lactic acid by simultaneous saccharification and fermentation.Rice bran is a cheap alternative to conventional raw materials like corn and wheat flour. Moreover, being an agricultural by-product, rice bran does not compete with food consumption. In the Philippines, around 1.5 million tons rice bran is produced every year. Even in Oriental Mindoro alone where the plant is to be situated, 26,500 tons rice bran is produced.This study aims to present a viable manufacturing process of lactic acid using rice bran as substrate.This design report aims to lay-out the complete process flow diagram of this process, compute for the design parameters and power requirements of equipment and evaluate the economic feasibility of the manufacturing process. The main part of the process flow diagram comes from the study of Akerberg and Zacchi, 2000 with the introduction of simultaneous saccharification and fermentation as a replacement to simple saccharification and fermentation. Several empirical equations and correlations were used in the design process, particularly those from Towler (2008), Foust (1964), Vogler & Todaro (1997) Riemann (2006). The economic feasibility of the process was computed using correlations given by Timmerhaus (1991).In this study, the computed return on equity for the production of lactic acid via simultaneous saccharification and fermentation is 23 percent while the computed payback period is 5.38 years. Thus, the use of the design profitable because of the ROE is well above the benchmark of 12%.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Lactic acid; Rice bran